Regeneration of the bone tissue in osteosynthesis with implants made of magnesium-based alloys in experiment - Golovakha, Maksim; Chorny, Vadim; Yatsun, Yevgeniy; Tertishny, Sergey; Dikiy, Konstantin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
Peculiarities in the regeneration of a fracture of the femoral bone after osteosynthesis with rods, made of ÌË-10 magnesium alloy, were studied in 12 pubescent rabbits. In control animals, a modelled fracture of the femur was followed by osteosynthesis with intramedullary fixing devices, made of stainless steel. When the animals were taken out of the experiment, the femur was sawn through the fracture area together with the graft. It was found out that the healing of femoral fractures in animals in conditions of using grafts, made of a modified magnesium alloy, did not differ from the processes of reparation, observed in controls. The consolidation of the fracture took place within the same terms and without any pathological disturbances.